1995
DOI: 10.3109/02713689508998519
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of goblet cell mucous secretion by activation of nerves in rat conjunctiva

Abstract: An epithelial debridement wound, as a stimulus to the cornea, causes conjunctival goblet cell mucous secretion in that eye. To determine if this stimulation of secretion is neurally mediated, rats were anesthetized and the local anesthetic lidocaine (1%) or buffer alone was administered topically and/or subconjunctivally for 15 min. A corneal epithelial debridement wound was made in one eye. The contralateral eye served as the control. After 5-120 min, animals were sacrificed and inferior bulbar conjunctival b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 11 publications
1
37
0
2
Order By: Relevance
“…This finding was in concordance with a recent study which found that a lidocaine analog significantly inhibited OVAinduced mucus secretion in mice [18]. A different study found that topical application of lidocaine inhibited mucous secretion [19]. Our finding further supports previous findings in which lidocaine suppressed goblet cells.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was in concordance with a recent study which found that a lidocaine analog significantly inhibited OVAinduced mucus secretion in mice [18]. A different study found that topical application of lidocaine inhibited mucous secretion [19]. Our finding further supports previous findings in which lidocaine suppressed goblet cells.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth noting that the number of mucin-containing goblet cells varies considerably between individuals and areas of the conjunctiva. Thus, to minimize variability, the same area of the conjunctiva was removed each time and for each experiment a basal and all concentrations of agonist were evaluated from each animal (Kessler et al, 1995;Dartt et al, 1996). Therefore, this limits the number of concentrations of agonists and antagonists that can be used.…”
Section: Measurement Of Goblet Cell Glycoprotein Secretion In Vitromentioning
confidence: 99%
“…Immediately after the rats were killed, the globes of both eyes were removed with the lids intact as previously described (Kessler et al, 1995). The globe was ®xed for 4 hr at 48C in 4 % formaldehyde in phosphate buffered saline (PBS, which contained 145 mM NaCl, 7 .…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations